Effects of the Mediterranean Diet or Nut Consumption on Gut Microbiota Composition and Fecal Metabolites and their Relationship with Cardiometabolic Risk Factors. Issue 19 (16th August 2021) - Galié, Serena; García‐Gavilán, Jesús; Camacho‐Barcía, Lucía; Atzeni, Alessandro; Muralidharan, Jananee; Papandreou, Christopher; Arcelin, Pierre; Palau‐Galindo, Antoni; Garcia, David; Basora, Josep; Arias‐Vasquez, Alejandro; Bulló, Mònica
Abstract : Scope: To examine whether a Mediterranean Diet (MedDiet) compared to the consumption of nuts in the context of a habitual non‐MedDiet exerts a greater beneficial effect on gut microbiota and fecal metabolites; thus, contributing to explain major benefits on cardiometabolic risk factors. Methods and Results: Fifty adults with Metabolic Syndrome are randomized to a controlled, crossover 2‐months dietary‐intervention trial with a 1‐month wash‐out period, following a MedDiet or consuming nuts (50 g day ‐1 ). Microbiota composition is assessed by 16S rRNA gene sequencing and metabolites are measured using Nuclear Magnetic Resonance (NMR) and liquid chromatography coupled to triple quadrupole mass spectrometry (LC‐qTOF) platforms in a targeted metabolomics approach. Decreased glucose, insulin and the homeostatic model assessment of insulin resistance (HOMA‐IR) is observed after the MedDiet compared to the nuts intervention. Relative abundances of Lachnospiraceae NK4A136  and an uncultured genera of Ruminococcaceae are significantly increased after the MedDiet compared to nuts supplementation. Changes in  Lachnospiraceae NK4A136  are inversely associated with insulin levels and HOMA‐IR, while positively and negatively with changes in cholate and cadaverine, respectively. Conclusions: Following a MedDiet, rather than nuts, induces a significant increase in  Lachnospiraceae NK4A136  and improves the metabolic risk. This genera seems to affect the bile acid metabolism and cadaverine which may account for the improvement in insulin levels. Abstract : Following a Mediterranean diet (MedDiet) rather than a regular diet supplemented with nuts increases the abundance of Lachnospiraceae NK4A136 which is associated with MedDiet benefits on insulin metabolism, partially explained by fecal cholate increases and cadaverine decreases.